2022
DOI: 10.3390/ijerph19138073
|View full text |Cite
|
Sign up to set email alerts
|

Getting to the Bottom of Saddle Sores: A Scoping Review of the Definition, Prevalence, Management and Prevention of Saddle Sores in Cycling

Abstract: Objectives: To summarise and map the existing evidence relating to the definition, prevalence, prevention and management of saddle sores within the literature and highlight research gaps. Design: Scoping review. Data Sources: Three databases were searched using an appropriate search strategy agreed on by the authors with the aid of an experienced medical librarian; these databases were MEDLINE, EMBASE and Web of Science. Eligibility Criteria: To be included in this review, studies must have made specific refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…11 Initially redness, chafing, pain, loss of sensation and folliculitis, and developing into ulceration and chronic unilateral swelling of the labia majora "bicyclist's vulva". 2,3,9,12 A 2022 systematic review into the prevalence of saddle sores reported them almost exclusively to be in males, however, the author accepts that this likely represents publication bias. 2 We have demonstrated that actually saddle sores are a significant problem in female cyclist.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…11 Initially redness, chafing, pain, loss of sensation and folliculitis, and developing into ulceration and chronic unilateral swelling of the labia majora "bicyclist's vulva". 2,3,9,12 A 2022 systematic review into the prevalence of saddle sores reported them almost exclusively to be in males, however, the author accepts that this likely represents publication bias. 2 We have demonstrated that actually saddle sores are a significant problem in female cyclist.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,9,12 A 2022 systematic review into the prevalence of saddle sores reported them almost exclusively to be in males, however, the author accepts that this likely represents publication bias. 2 We have demonstrated that actually saddle sores are a significant problem in female cyclist. Effective management of early symptoms may prevent the more significant symptoms developing that potentially require surgical management.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations